Warburg effect(s)—a biographical sketch of Otto Warburg and his impacts on tumor metabolism - Otto, Angela M. (Cancer & metabolism, 2016)
Virtually everyone working in cancer research is familiar with the “Warburg effect”, i.e., anaerobic glycolysis in the presence of oxygen in tumor cells. However, few people nowadays are aware of what lead Otto Warburg to the discovery of this observation and how his other scientific contributions are seminal to our present knowledge of metabolic and energetic processes in cells. Since science is a human endeavor, and a scientist is imbedded in a network of social and academic contacts, it is worth taking a glimpse into the biography of Otto Warburg to illustrate some of these influences and the historical landmarks in his life. His creative and innovative thinking and his experimental virtuosity set the framework for his scientific achievements, which were pioneering not only for cancer research. Here, I shall allude to the prestigious family background in imperial Germany; his relationships to Einstein, Meyerhof, Krebs, and other Nobel and notable scientists; his innovative technical developments and their applications in the advancement of biomedical sciences, including the manometer, tissue slicing, and cell cultivation. The latter were experimental prerequisites for the first metabolic measurements with tumor cells in the 1920s. In the 1930s–1940s, he improved spectrophotometry for chemical analysis and developed the optical tests for measuring activities of glycolytic enzymes. Warburg’s reputation brought him invitations to the USA and contacts with the Rockefeller Foundation; he received the Nobel Prize in 1931. World politics and world wars heavily affected Warburg’s scientific survival in Berlin. But, after his second postwar recovery, Warburg’s drive for unraveling the energetic processes of life, both in plants and in tumor cells, continued until his death in 1970. The legacy of Otto Warburg is not only the Warburg effect, but also the identification of the “respiratory ferment” and hydrogen-transferring cofactors and the isolation of glycolytic enzymes. His hypothesis of respiratory damage being the cause of cancer remains to be a provocative scientific issue, along with its implications for cancer treatment and prevention. Warburg is therefore still stimulating our thinking, as documented in a soaring increase in publications citing his name in the context of tumor metabolism.